Future Development of Renewable Energy in Russia: A Case of Solar Power - Rausser, Gordon; Chebotareva, Galina; Smutka, Luboš; Strielkowski, Wadim; Shiryaeva, Julia (Frontiers in Energy Research, 2022)
Currently, there is a growing number of studies related to assessing the cost-effectiveness of renewable energy projects around the world. This topic is also very relevant for the Russian energy market that is otherwise dominated by oil and gas. The Russian Ministry of Energy forecasts that local power plants running on the renewable energy sources (RES) may not become economically efficient until 2025 or later. However, a research question arises: is it possible to effectively implement RES projects in Russia without any state support? In order to answer this question, we need to assess the economic feasibility of seven scenarios for the construction of a solar power plant in the Orenburg region of Russia. The methodological basis of this work is the method of investment analysis based on the calculation of discounted indicators: net present value, payback period and internal rate of return of the project. We derived the scenarios on the basis of an analysis of the features of electricity and capacity generation in the Orenburg region, the existing options for joining the trading system of the energy market, as well as the availability of the Russian government support and funding for the solar energy projects. Our results demonstrate that the economic feasibility of the development of renewable energy in Russia can become a reality. Moreover, the two project scenarios without government support also yielded a positive economic effect. Our results have practical significance and will be used in developing an approach to creating a profile of regions in terms of the advancements of renewable energy, as well as in developing strategies for the incentives of this sector in Russia.